2002
DOI: 10.1063/1.1468275
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic surface photovoltage spectroscopy

Abstract: We present a microscopic surface photovoltage spectroscopy method. It is based on a tunable illumination system combined with a kelvin probe force microscope, which measures the contact potential difference between a sample surface and a tip of an atomic force microscope. By measuring the contact potential difference as a function of illumination wavelength, the whole surface photovoltage spectrum of a semiconductor sample is obtained with submicrometer spatial resolution. This resolution can be as high as 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…Shifts of the surface potential (Fig. 3) are attributed to generation and/or redistribution of free charge carriers 10, 13–15. Similar KFM studies on polypyrrole‐diamond heterojunction showed very fast (<1 s) charge carrier generation and recombination.…”
Section: Discussionsupporting
confidence: 57%
“…Shifts of the surface potential (Fig. 3) are attributed to generation and/or redistribution of free charge carriers 10, 13–15. Similar KFM studies on polypyrrole‐diamond heterojunction showed very fast (<1 s) charge carrier generation and recombination.…”
Section: Discussionsupporting
confidence: 57%
“…Additionally, although KPFM studies highlighted in this review show light‐induced changes in CPD, there is no study examining this change as a function of wavelength of the incident radiation. This type of study has been done on the GaP p–n junction, but is lacking for photovoltaic materials. For OHPs, comparing this type of data with external quantum efficiency measurements of the device will provide a more detailed picture of how morphology variations in the OHP thin film are affecting its optoelectronic properties and, ultimately, solar cell PCE.…”
Section: Discussionmentioning
confidence: 99%
“…Photovoltage measurements on the cross section using KPFM techniques have also been conducted on various types of solar cells such as III–V multi-junctions [ 9 ] or CuIn x Ga (1 − x ) Se 2 (CIGS) heterojunctions [ 10 ] revealing photogeneration effects and local surface potential shifts with the illumination intensity. The influence of the wavelength of illuminating light has also been reported [ 11 ]. More recently, it has been shown that nanoscale photovoltage measurements using a pulsed light source enable to extract the photocarrier lifetime [ 12 ].…”
Section: Introductionmentioning
confidence: 99%